Совершенствование проточной части ЦНД мощной паровой турбины с учетом протечек - Солодов, Валерий Григорьевич; Конев, Владимир Афанасьевич (НТУ "ХПИ", 2017)
Рассмотрены основные результаты численных исследований проточной части цилиндра низкого давления (ЦНД) турбины К-1250-6,9/25 с улучшенными относительно ранее исследованного исходного варианта геометрическими параметрами отсека первых трех ступеней. Исследования проведены с учетом отборов пара, протечек через надбандажные и диафрагменные уплотнения, разгрузочные отверстия в дисках и отсоса влагоемкого пара из периферийных межвенцовых зазоров последних ступеней. Представлены некоторые методические аспекты и сравнительные результаты численного эксперимента.

The results of computational and engineering developments and numerical studies of low pressure cylinder of five stages are represented, taking into account the steam extraction, leakages under the diaphragms, shroud seals and discharge openings in the disks of the turbine K-1250-6.9/25. All the computations were based on the model of one speed wet steam flow without droplets and super cooling was not taken into account. The sectorial approach was applied to description of the interaction of the inlet pipe, the group stages and exhaust hood. The stages were considered in steady state formulation. The initial data and boundary conditions were taken basing on thermal design of "TURBOATOM". Some methodological aspects and the directions of improving of studied facilities by numerical experiment by MTFS® code are discussed.
Improvement of the L.P.C. flow path of powerful steam turbine unit with the account of leaks
Keywords: численная модель; отборы; уплотнения; численный эксперимент; flow path; numerical model; extraction; seals